Proton release by toods of Medicago murex and Medicago sativa growing in acid conditions, and implications for rizosphere pH changes and nodulation at low pH - Cheng, Y. W.; Howieson, J.; O'Hara, G.; Watkin, Elizabeth (Elsevier ltd, 2004)
Medicago murex nodulates faster and produces more nodules than Medicago sativa in acidic sandy soils. Experiments using a ‘root mat’ approach and videodensitometry examined pH changes in the rhizospheres of nitrate-fed plants of M. murex and M. sativa. Using the ‘root mat’ approach with soil disks of pH 4.49, M. sativa cv. Aquarius acidified its rhizosphere by approximately 0.2–0.4 pH-units within 4 d, while M. murex cv. Zodiac did not acidify its rhizosphere. Rates of H+ release were higher from M. sativa than from M. murex. Videodensitometry of roots embedded in agarose of pH 4.5 showed that the mature parts of the tap-root of both species exuded OH− ions, but was approximately twofold more in M. murex than in M. sativa. Consequently, young parts of the M. sativa rhizosphere were less alkaline than that of M. murex. It is suggested that the difference in nodulation response between the two species at low pH may be related to the different patterns of rhizosphere acidification: the stronger rhizosphere acidification of M. sativa being less favourable for survival and growth of Sinorhizobium medicae. The higher rate of rhizosphere acidification by M. sativa roots may be related to its genetic characteristics including greater relative root growth rate and greater sensitivity to acidity in comparison to M. murex.